Predictive factors for anemia response to erythropoiesis‐stimulating agents in myelofibrosis. (19th January 2017) - Hernández Boluda, Juan‐Carlos; Correa, Juan‐Gonzalo; García‐Delgado, Regina; Martínez‐López, Joaquín; Alvarez‐Larrán, Alberto; Fox, María‐Laura; García‐Gutiérrez, Valentín; Pérez‐Encinas, Manuel; Ferrer‐Marín, Francisca; Mata‐Vázquez, María‐Isabel; Raya, José‐María; Estrada, Natalia; et al.
Abstract: Objective: Erythropoiesis‐stimulating agents (ESAs) are commonly used to treat the anemia of myelofibrosis (MF), but information on the predictors of response is limited. Methods: Results of ESA therapy were analyzed in 163 MF patients with severe anemia, most of whom had inadequate erythropoietin (EPO) levels (<125 U/L) at treatment start. Results: According to the revised criteria of the International Working Group for Myelofibrosis Treatment and Research, anemia response was achieved in 86 patients (53%). Median response duration was 19.3 months. In multivariate analysis, baseline factors associated with a higher response rate were female sex ( P =.007), leukocyte count ≥10×10 9 /L ( P =.033), and serum ferritin <200 ng/mL ( P =.002). Patients with 2 or 3 of the above features had a significantly higher response rate than the remainder (73% vs 28%, respectively; P <.001). Over the 373 patient‐years of follow‐up on ESA treatment, nine patients developed thrombotic complications (six arterial, three venous), accounting for 2.41 events per 100 patient‐years. Survival time from ESA start was longer in anemia responders than in non‐responders ( P =.011). Conclusion: Besides the already established predictive value of EPO levels, these data can help to identify which MF patients are more likely to benefit from ESA treatment.